OP04 Circulating levels of the long pentraxin PTX3, but not hepatocyte derived C-reactive protein, correlate with severity following human acute liver injury. (16th November 2010) - Craig, D; Lee, P; Pryde, E A; Walker, S; Beckett, G; Hayes, P; Simpson, K
Abstract : Introduction: The innate immune response may underpin the development of multiorgan failure following acute liver injury, particularly following paracetamol overdose (POD). Pentraxin 3 (PTX3) is a long pentraxin induced by interleukin (IL)-10, and produced by vascular endothelium, macrophages, and myeloid dendritic cells. PTX3 has diverse effector functions including opsonisation, clearance of apoptotic debris, and tissue repair. Aim: To measure levels of PTX3 and C-reactive protein (CRP), a hepatocyte derived short pentraxin involved in the acute phase response, in patients with acute liver injury. Method: Consecutive patients admitted to the Royal Infirmary of Edinburgh with acute liver injury (ALT>1000 IU/l and coagulopathy) were enrolled. PTX3 and CRP levels were measured by ELISA and turbimetry, respectively. Results: A total of 60 patients (48 POD, 12 non-POD) were enrolled. 28/48 (58.3%) of POD and 8/12 (66.7%) non-POD patients developed hepatic encephalopathy (HE), and therefore acute liver failure. As expected, admission PTX3 levels correlated strongly with IL-10 (Spearman's r=0.641, p<0.001), but also correlated with INR (r=0.728, p<0.001) and ALT (r=0.554, p<0.001), but not with CRP (r=-0.124, p=0.35). Admission PTX3 levels were significantly higher in POD patients with HE (median (interquartile range) 329.4 (77.7–738.1 ng/ml)) compared with POD patients without HE (46.1 (6.1–172.4) ng/ml, p=0.0005), or with non-POD patients (23.7 (9.1–40.0) ng/ml, p=0.004). PTX3 levels in POD patients who died or required emergency liver transplantation (LT) (772.9 (268.2–848.7) ng/ml) were significantly higher compared with spontaneous survivors (81.1 (12.0–437.1), p<0.0001), with an area under the receiver operator characteristic curve of 80.3 (95% CI 67.1 to 93.4). Admission PTX3 levels in POD patients correlated with admission APACHE II (r=0.398, p=0.006) and SOFA (r=0.536, p<0.001) scores, and were higher in POD patients who developed the systemic inflammatory response syndrome (SIRS 306.4 (113.9–764.7) ng/ml, no SIRS 50.5 (6.66–297.7) ng/ml, p=0.001). Conversely, admission CRP levels were significantly decreased in POD patients (6.05 (3.93–15.38) mg/l) compared with non-POD patients (17.6 (3.9–15.4) mg/l, p=0.011). There were no significant differences in CRP levels between POD patients who died/required LT (5.2 (4.3–15.9) mg/l) and survivors (7.9 (3.5–15.7) mg/l, p=0.820). Conclusion: These data suggest that the humoral arm of the innate immune system plays an important role in the pathogenesis of multiorgan failure following POD. PTX3 may have a role as a novel prognostic marker in this condition.